A systematic review of biosensors suitable for environmental biomonitoring of heavy metal water pollution in the Philippines - Peñafiel, Winona Abidin (Animo Repository, 2022)
Heavy metal pollution with concentrations much above the prescribed limits set by the Department of Environment and Natural Resources have been reported at various water bodies in the Philippines. So far, conventional methods that are usually time consuming and expensive equipment/instruments have been used for environmental biomonitoring of the heavy metals in the Philippines. Hence, the use of environmental biosensors is also a suggested alternative in measuring heavy metal concentrations in different freshwater bodies in the country. This systematic review used existing literature from NCBI, PubMed, PLOS One, Science Direct, and Elsevier using PRISMA guidelines to determine the most suitable biosensors to detect heavy metals namely- Arsenic, Copper, Cadmium, Lead, and Mercury based on two criteria namely – Limit of Detection (LOD) and selectivity. A total of 57 journals were used in the study which were subjected to a quality assessment using the JBI appraisal checklist. The LOD for all the biosensors was re-calculated in ppm units and the biosensors were graded and grouped based on the type of transducers, transduction methods, bioreceptors, interfering ions based on the information gathered from selected articles. The selection of the most appropriate environmental biosensor was conducted by performing an elimination process wherein the researchers ranked each included heavy metal biosensor for their suitability based on the selection criteria (LOD, selectivity, and number of applicable freshwater bodies).The systematic review analysis suggested that optical biosensors were most suitable for the detection of all five (5) heavy metals, Arsenic, Cadmium, Copper, and Lead in the context of levels of heavy metal pollution in the Philippines’ water bodies. The information can be used as baseline data for constructing and using the appropriate biosensors for environmental biomonitoring of heavy metals in water bodies in the Philippines.